A rare case report of transient pancytopenia in a patient with coronavirus disease 2019 (Indian Journal of Case Reports, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for coronavirus disease 2019 (COVID-19) infection. The ongoing pandemic of COVID?19 has sought the attention of clinicians and researchers to investigate and describe its various pathological aspects. Infection with SARS-CoV-2 and the resulting COVID-19 can affect virtually any organ of the human body, including the bone marrow which, in turn, causes pancytopenia. Diagnosing pancytopenia in the setting of COVID-19 infection is challenging and requires ruling out all other potential causes of pancytopenia. Herein, we report a rare case of severe pancytopenia secondary to COVID-19 infection that developed severe transient pancytopenia which improved with conservative management.